Yield vulnerability of low-income smallholders to pollinator declines in Brazil is biome-dependent - Willams Oliveira; Rafaella Guimarães Porto; Oswaldo Cruz-Neto; Marcelo Tabarelli; Blandina Felipe Viana; Carlos A. Peres; Ariadna Valentina Lopes (PLoS ONE, 2025)
Habitat loss and degradation, mainly driven by agricultural expansion and intensification, alter ecological processes, ecosystem services and human well-being at a global scale. Pollinator populations in degraded agricultural areas tend to collapse, which in turn can reduce the effective pollination of agricultural crops and food production, particularly in leading food producing countries, such as Brazil. We sought to understand how the vulnerability to pollinator failure and the economic value of pollination (EVP) are associated with farmland size, farmer income, habitat loss, and the size of the human footprint. We also examine socioeconomic predictors related to income inequality levels across Brazilian municipalities and phytogeographic domains. We show that 58% of all leading crops in Brazil are dependent to some degree on animal pollination, and agricultural production in 96.8% of all municipalities is at least partly vulnerable to pollinator failure. Soybean, coffee, cotton, tomato and cocoa accounted for 84% of the total economic valuation of cropland pollination in Brazil, with soybean alone representing more than half of this value. Including soybean, vulnerability and EVP were positively correlated with the Human Development Index (HDI), Gross Domestic Product (GDP), habitat loss, and farmland size. On the other hand, these key indicators were negatively associated with the human footprint and the proportion of low-income farmers. Excluding soybean, however, vulnerability increased across low-income municipalities, particularly across the Atlantic Forest, Cerrado, and Caatinga, revealing strong biome contrasts. Overall, EVP was consistently reduced in areas under heavier human footprint, suggesting that anthropogenic pressures reduce pollination benefits. Our results also show that soybean cultivation masks underlying social and regional disparities in agricultural vulnerability. Thus, the evaluation of pollination risks can be masked by commodity production. Enhancing ecological processes and promoting diversified, pollinator-friendly agriculture may strengthen food production, particularly for tropical low-income farmers in vulnerable regions, while contributing to ecosystem service provision and human well-being.